2020
DOI: 10.17645/up.v5i1.2523
|View full text |Cite
|
Sign up to set email alerts
|

Building Adaptive Capacity through Learning in Project-Oriented Organisations in Infrastructure Planning

Abstract: Transport infrastructure networks are currently being challenged by rapidly changing contexts, such as climate change, new IT and mobility technologies, ageing infrastructure, demographic changes and growing engagement of stakeholders. These challenges call for an adaptive management approach in infrastructure planning. Apart from making the physical infrastructure more adaptive, organisational adaptive capacity is currently being discussed in both literature and practice. The literature describes learning as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 34 publications
(69 reference statements)
3
27
0
Order By: Relevance
“…Boyer and Roth (2005) found that different groups can join to form “a group of groups” (Boyer and Roth, 2005, p. 349), thereby expanding learning through relatively weak relationships between separate groups. De Groot et al (2020) described that project-oriented organisations deliberately group projects into programmes to improve overall performance. Although most programmes are not intended to improve learning, they can provide the link for inter- and meta-project learning organisation (Buijs, 2010; De Groot et al , 2020).…”
Section: Theoretical Framework: Programme Management and Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…Boyer and Roth (2005) found that different groups can join to form “a group of groups” (Boyer and Roth, 2005, p. 349), thereby expanding learning through relatively weak relationships between separate groups. De Groot et al (2020) described that project-oriented organisations deliberately group projects into programmes to improve overall performance. Although most programmes are not intended to improve learning, they can provide the link for inter- and meta-project learning organisation (Buijs, 2010; De Groot et al , 2020).…”
Section: Theoretical Framework: Programme Management and Learningmentioning
confidence: 99%
“…However, team learning – “the process of aligning and developing the capability of the team to create the results its members truly desire” (Senge, 1990, p. 236) – in projects is strongly affected by the focus on project results. De Groot et al (2020) argued that the predominantly problem-oriented and internal focus of project teams hinders learning to other project teams and their parent organisation. Projects are temporary constructs for delivering predefined results within set conditions of time, scope and budget (Gemünden et al , 2018; Pellegrinelli, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, as Willems et al (2020) also point out, and in line with classic analyses such as (Scott, 1998), once engineeringdominated public organizations are in charge of complex projects, they are hard to dislodge, and the associated discourses on expertise, steering, and participation are hard dismantle. De Groot et al (2020) give central place to the project level of organization, with in some cases projects serving as new entities coordinating various organizations, and in other cases as more rudimentary information exchange platforms coordinating actors within the organization. The authors observe the general success of projects in terms of local adaptation but also the distance between project discourse and the mother organizations, or higher management (echoing the Luhmannian analysis of Seidl, 2016; see also Van Assche & Verschraegen, 2008).…”
Section: Learning and Comparison In High Complexity Environmentsmentioning
confidence: 99%
“…De Groot et al (2020) and Willems et al (2020) both bump into the central issue of complexity in current governance. Complexity is both necessary and problematic in the search for answers to big problems in democratic societies.…”
Section: Learning and Comparison In High Complexity Environmentsmentioning
confidence: 99%